Vibration control device for steel tubular towers of Horizontal Axis Wind Turbines - Lima,Douglas Mateus de (2019)
Abstract This paper presents and discusses the design of a vibration control device for a 120 m high steel tubular tower of onshore Horizontal Axis Wind Turbine (HAWT). The tower is modeled using beam (own code), and shell and solid finite elements (via ANSYS). The Dynamic Vibration Absorber (DVA) is designed to be attached to the tower top, aiming to analyze Tuned Mass Damper (TMD), Active Mass Damper (AMD), and Hybrid Mass Damper (HMD). The theory proposed by Den Hartog is used to determine the coefficients of the absorber and the Linear Quadratic Regulator (LQR) is applied to obtain the optimal control variables introduced by the hydraulic actuators. The HMD, the main contribuition of this paper, reaches excellent levels of vibration reduction for the tower submitted to harmonic actions, in a transient and permanent (stationary) regime, resonant to the first vibration mode of the structure without control.